Serbia's New Growth Agenda : Removing Regulatory Barriers to Competition - World Bank (World Bank, Washington, DC, 2020)
This note outlines barriers to competition in product markets based primarily on the screening of Serbian regulations using the OECD Product Market Regulation methodology and comparison to regulations in the OECD. The note focuses on topics covered by the 2018 OECD-WBG product market regulation (PMR) indicators such as regulation of network industries, professional services, state-owned enterprises, and restrictions on foreign businesses. The OECD-WBG product market regulation indicators are a screening tool that measure the degree to which regulations promote or inhibit competition. The indicators rely on qualitative information on over 1,000 features of economy-wide and sectoral regulations. The qualitative information is collected and coded based on a standardized questionnaire and later aggregated into quantitative scores that run from 0 (least restrictive) to 6 (most restrictive) using standardized weights. The analysis in this note relies on primary data for Serbia collected by the World Bank Group and comparative data for other countries collected by the OECD. To ensure comparability across countries the data is current as of January 1, 2018. The data has been collected throughout 2018 and the indicators included in this report are as of July 2019. The PMR indicators for Serbia have been calculated as part of the partnership between OECD and WBG Markets and Competition Policy Team and the primary data has been collected in collaboration with more than 30 public and private institutions in Serbia.